Rescue of embryonic stem cells from cellular transformation by proteomic stabilization of mutant p53 and conversion into WT conformation - Rivlin, Noa (National Academy of Sciences, 2014)
p53 is a well-known tumor suppressor that is mutated in over 50% of human cancers. These mutations were shown to exhibit gain of oncogenic function compared with the deletion of the gene. Additionally, p53 has fundamental roles in differentiation and development; nevertheless, mutant p53 mice are viable and develop malignant tumors only on adulthood. We set out to reveal the mechanisms by which embryos are protected from mutant p53–induced transformation using ES cells (ESCs) that express a conformational mutant of p53. We found that, despite harboring mutant p53, the ESCs remain pluripotent and benign and have relatively normal karyotype compared with ESCs knocked out for p53. Additionally, using high-content RNA sequencing, we show that p53 is transcriptionally active in response to DNA damage in mutant ESCs and elevates p53 target genes, such as p21 and btg2. We also show that the conformation of mutant p53 protein in ESCs is stabilized to a WT conformation. Through MS-based interactome analyses, we identified a network of proteins, including the CCT complex, USP7, Aurora kinase, Nedd4, and Trim24, that bind mutant p53 and may shift its conformation to a WT form. We propose this conformational shift as a novel mechanism of maintenance of genomic integrity, despite p53 mutation. Harnessing the ability of these protein interactors to transform the oncogenic mutant p53 to the tumor suppressor WT form can be the basis for future development of p53-targeted cancer therapy.